2008
DOI: 10.1002/lsm.20625
|View full text |Cite
|
Sign up to set email alerts
|

In vitro resistance of articular chondrocytes to 5‐Aminolevulinic acid based photodynamic therapy

Abstract: 5-ALA-PDT might represent a treatment strategy in inflammatory joint diseases without endangering the cartilage function. However, further in vitro and in vivo experiments are required to confirm this data in the authentic environment of chondrocytes, the articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…14 Regarding the effect on collagen, no changes in synthesis of collagen type II, the major connective tissue component of ear cartilage, has been observed when chondrocytes were treated in vitro with ALA-PDT. 15 Nevertheless, Park et al 16 have demonstrated that after 1 month of treatment with ALA-PDT in human skin, the total collagen volume in the dermis significantly increased, with expression of type I and III procollagen; this could explain the excellent cosmetic results in our patients.…”
Section: Commentmentioning
confidence: 64%
See 1 more Smart Citation
“…14 Regarding the effect on collagen, no changes in synthesis of collagen type II, the major connective tissue component of ear cartilage, has been observed when chondrocytes were treated in vitro with ALA-PDT. 15 Nevertheless, Park et al 16 have demonstrated that after 1 month of treatment with ALA-PDT in human skin, the total collagen volume in the dermis significantly increased, with expression of type I and III procollagen; this could explain the excellent cosmetic results in our patients.…”
Section: Commentmentioning
confidence: 64%
“…Regarding the effect on cartilage, it has been shown that chondrocytes are not destroyed by ALA-PDT, whereas a decrease in the proportion of viable cells occurs in osteoblasts and synovial cells. 15 In addition, PDT has been shown to modulate in vitro cartilage metabolism, activating a chondroprotective program in photosensitized cartilage in the context of osteoarthritis. 17 In our patients with CDNH, topical application of methyl aminolevulinate on the lesions resulted in a moderate fluorescence.…”
Section: Commentmentioning
confidence: 99%
“…In vitro study reported that the highest levels of PpIX fluorescence during flow cytometry measurements were detected in osteoblasts, followed by synovial cells and chondrocytes [25]. Also, the relative resistance of the chondrocytes to 5-ALA-PDT in comparison with cells derived from synovial tissues had been shown [25]. However, there is no data about the induction of endogenous porphyrins and the accumulation pharmacokinetics in human cartilage tissue of RA or OA patients after the application of ALA or its derivatives.…”
Section: Introductionmentioning
confidence: 93%
“…This minimally invasive PDT approach could serve as an attractive alternative to the surgical synovectomy, because it usually results in little or no scarring and presumably would http shorten a rehabilitation period and reduce the need for subsequent physiotherapy. Resent findings showed that, besides inflamed synovium, endogenous porphyrins were also detected in cartilage tissues of rabbit rheumatoid arthritis model in vivo [23,24] and chondrocytes in vitro [25] after the application of ALA or its methyl ester (ALA-Me). In vitro study reported that the highest levels of PpIX fluorescence during flow cytometry measurements were detected in osteoblasts, followed by synovial cells and chondrocytes [25].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation